396 Young Scholar Award Talk: The Selection of Potential Probiotics for Bovine Respiratory Disease Treatment and Prevention. (21st September 2022) - Howe, Samantha M; Chai, Jianmin; Usdrowski, Hunter M; Capik, Sarah; Kegley, Beth B; Richeson, John T; Powell, Jeremy; Zhao, Jiangchao
Abstract: Bovine Respiratory Disease (BRD) is the most devastating disease affecting cattle producers in North America. Vaccines and antimicrobials are commonly used to prevent and treat BRD. However, it is still a growing problem. The four common BRD opportunistic pathogens, Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and Mycoplasma bovis, are present in the upper respiratory tract of healthy cattle as well, and how they move to the lung are unknown. The apparent role of the respiratory microbiome in BRD has led to many microbiome studies. However, most culture-independent studies have focused on the opportunistic pathogens, and little is known about the potential bacterial probiotics in the prevention and treatment of BRD. This study aims to identify potential probiotics to treat and prevent BRD by analyzing respiratory microbiotas (nasal swabs (NS): healthy: n=94, BRD: n=94; nasopharyngeal swabs (NPS): healthy: n=25, BRD: n=36; and bronchoalveolar lavage (BAL): healthy: n=22, BRD: n=29) from clinically healthy calves at feedlot entrance and calves at BRD diagnosis. Amplicon sequence variants (ASVs) were classified as potential probiotics if selected as a top predictor by a machine learning technique (random forest) and significantly more abundant in healthy controls (log2fold change ≥ 2 and P<0.05) based on DESeq2. ASV98_Corynebacterium was a potential probiotic in all three locations. ASV121_JG30-KF-CM45_unclassified, ASV32_Corynebacterium, and ASV64_Serinicoccus were potential probiotics in NPS and BAL. Additional taxa were potential probiotics in a single location, including ASV114_Streptococcus_luteciae and ASV233_Facklamia in NS; and ASV150_Facklamia, ASV26_Corynebacterium, ASV306_Facklamia, and ASV44_Dietzia in NPS. SPARCC network analysis revealed that ASV114_Streptococcus_luteciae was the top hub taxa in healthy calves' NS, and ASV32_Corynebacterium and ASV26_Corynebacterium were in the top five hub taxa of healthy calves' NPS, indicating that these ASVs are key members of their respective communities. Furthermore, SPARCC found ASV32_Corynebacterium is negatively correlated with ASV2_Mycoplasma (-0.25) in NS and ASV5_Mycoplasma_hyorhinis (-0.23) in NPS (P <0.05). Additionally, ASV26_Corynebacterium is negatively associated with ASV62_Ureaplasma (-0.37) and ASV5_Mycoplasma_hyorhinis (-0.21) in NPS and ASV12_Histophilus_somni in (-0.29) in BAL (P <0.05).